PERFORMANCE ANALYSIS OF URBAN ROADS JALAN A. YANI KM. 34, BANJARBARU - Idham Kholid; Rosehan Anwar (Universitas Lambung Mangkurat, 2017)
Banjarbaru is one of the major cities in southern Kalimantan. To support the improvement of the economy in the city Banjarbaru certainly one of the factors that influence is the road infrastructure in order to facilitate social activities, economy as well as the flow of goods and services. Jalan Ahmad Yani km. 34 Banjarbaru merupaka road sections that describe the traffic conditions Banjarbaru so it is important to know the performance of these roads now and in the future datang.Ruas Jalan A. Yani km 34 there is an area surrounding shopping area and the market. Therefore, it is necessary to predict the performance of the road section to the increasing number of motor vehicles in the future, as well as alternative treatment to break down these roads congestion problem.The method used in order to obtain the performance of road A. Yani km MKJI 1997.Dari 34 refers to the survey conducted, the data obtained Volume (V), travel time, as well as side constraints. As well as geometric data also obtained the necessary roads and secondary data, the number of urban dwellers Banjarbaru to complete the data to a multiplier to seek capacity.From the analysis of the data later obtained a maximum current capacity of 3207.60 Banjarmasin Banjarbaru-smp / h and a maximum current capacity of 3239,676 Banjarbaru Banjarmasin-smp / hour. Later obtained also the highest volume flow-Banjarmasin Banjarbaru amounted to 2071.2 smp / hour and the flow of 2093.7 Banjarbaru Banjarmasin-smp / hour. So we get the highest for both current DS of 0.64 with ITP B.Kemudian made predictions and found that the performance of road A. Yani km 34 worsen in the next three years and should be handling. Handling taken include the widening of the road and traffic diversion on busy hours on the road ringan.Pelebaran vehicles intended to increase road capacity while traffic diversion intended to volume decreases.Keywords: MKJI 1997, Prediction, Solutions.